The Role of Moral and Legal Education in Students’ Socialization and its Methodological Foundations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the role and significance of moral and legal education in the social development of students. The methodological foundations, principles, methods, and tools of moral and legal education are examined. The pedagogical conditions for shaping moral values, legal awareness, and culture among students are identified. The article aims to enhance the social activity of students, ensure their adaptation to society, and prevent offenses.